Identidad y personalidad - Ramos Ramos, Hugo Alexander (2019)
The session about reflective method and important of personality and identity in society as human beings. It was done in the area of personal information and civic, for students of second grade in Pedro M. Urea high school._x000D_ The purpose of the session is the reflection and the importance of personality and identity to fase lifes problems. It was plane through reflective method uses and its different studies